Augmented reality TV studio - Ng, Qi Ming (Nanyang Technological University, 2020)
Augmented reality has gained its popularity over the past few years. Due to the improvement in both hardware and software, an entry level smartphone can support Augmented Reality. The application of augmented reality can be found in many industries today. Through augmented reality, users can have a better understand of the topic being portrayed. The objective of this project is to design augmented reality application for the news media industry using Wikitude’s SLAM AR technology. SLAM allows instant tracking of plane continuously. Through continuous instant tracking, the application allowed 3D objects to be added into the news broadcasting scene to provide an enriched viewing experience to the viewers. In Chapter 2, this report covered the introduction of SLAM’s instant tracking feature. It includes the UI, overall design process, setup, 3D object spawning, moving, rotating and scaling process implementation. In addition, the overall functionality on how the application will be implemented in the news media industry is provided. In chapter 3, this report covered on object synchronization from one device to another through Unity Networking. When a 3D object is spawned from the host’s device, it will be reflected on another device. Similarly, the coordinates for the 3D object, will be synchronized from one device to another. To further improve on this application, video streaming and recording features could be implemented. Some 3D objects can have play back movement as well. With these features, it will further enhance the user viewing experience.